Activated Cassava Leaves As Low-Cost Adsorbent to Remove Dyes From Water - Chairunnisa Chairunnisa; Yuni Lisafitri; Mariyam Mariyam (Journal of Science and Applicative Technology, 2022)
In this study, activated cassava leaves were prepared using NaCl (CLN) and KOH (CLK) as novel and low-cost materials for removing dyes from water. The prepared materials were characterized using Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The adsorption experiments were carried out under different conditions of initial dye concentration (50 – 600 ppm), pH solution (4 – 10), and contact time (1 – 180 min) under room temperature. The adsorption kinetics has been studied using the pseudo-first and pseudo-second-order. The equilibrium isotherms have been analyzed using the Langmuir and Freundlich models. The adsorption kinetics of methylene blue onto activated cassava leaves follows a pseudo-second-order model. According to the isotherm study, the Langmuir model shows the best fitting results with the maximum adsorption capacity of 217.39 mg/g and 416.66 mg/g for cassava leaves that were activated by NaCl and KOH, respectively.